Thrombotic Microangiopathy with Severe Proteinuria Induced by Lenvatinib for Radioactive Iodine-Refractory Papillary Thyroid Carcinoma - Yasuko Hyogo; Naomi Kiyota; Naoki Otsuki; Shunsuke Goto; Yoshinori Imamura; Naoko Chayahara; Masanori Toyoda; Ken-ichi Nibu; Toshiki Hyodo; Shigeo Hara; Hiroo Masuoka; Toshihiko Kasahara; et al. (Case Reports in Oncology, 2018)
Standard therapy for radioactive iodine (RAI)-refractory differentiated thyroid cancer (DTC) is multi-targeted kinase inhibitors (m-TKIs), represented by sorafenib and lenvatinib. One of the main target molecules of m-TKIs is vascular endothelial growth factor receptor (VEGF-R). m-TKIs are known to cause adverse reactions such as hypertension and proteinuria as a class effect. In particular, proteinuria is thought to result from vascular endothelial damage and podocytopathy in glomeruli, and the development of thrombotic microangiopathy (TMA) has been reported for VEGF inhibitors. We encountered a patient with RAI-refractory (RR) papillary thyroid carcinoma (PTC) who developed proteinuria and renal dysfunction due to lenvatinib. Renal biopsy demonstrated that these changes were caused by TMA. To our knowledge, this is the first reported case of TMA due to lenvatinib in a Japanese patient with RR-PTC. A 70-year-old woman developed proteinuria, renal impairment and hypertension while receiving lenvatinib for RR-PTC. Her proteinuria and renal damage continued to worsen despite dose reductions and dose interruptions. Renal biopsy was consistent with the chronic type of TMA. These findings indicate that TMA is a possible cause of proteinuria due to lenvatinib, as has been reported for the VEGF inhibitors.